2009
DOI: 10.1111/j.1440-1797.2008.01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary levels of epidermal growth factor, interleukin‐6 and monocyte chemoattractant protein‐1 may act as predictor markers of renal function outcome in immunoglobulin A nephropathy

Abstract: Urinary MCP-1, IL-6 and EGF levels may represent histology in IgAN. EGF excretion can be a predictive marker and its serial measurements may give information about disease outcome and the effect of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 33 publications
1
62
1
2
Order By: Relevance
“…However, little information is available regarding the implication of urinary proinflammatory chemokine levels in pediatric-onset renal diseases (Watson et al 2012). So far, it has been reported that the urinary MCP-1 concentration may predict disease activity in adulthood IgAN and LN (Stangou et al 2009(Stangou et al , 2013Abujam et al 2013). Interestingly, Stangou et al (2009) have reported that the urinary MCP-1 concentration is significantly correlated with the degree of interstitial fibrosis, which is an index reflecting the histological chronicity, in adult patients with IgAN.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, little information is available regarding the implication of urinary proinflammatory chemokine levels in pediatric-onset renal diseases (Watson et al 2012). So far, it has been reported that the urinary MCP-1 concentration may predict disease activity in adulthood IgAN and LN (Stangou et al 2009(Stangou et al , 2013Abujam et al 2013). Interestingly, Stangou et al (2009) have reported that the urinary MCP-1 concentration is significantly correlated with the degree of interstitial fibrosis, which is an index reflecting the histological chronicity, in adult patients with IgAN.…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively, recent studies have reported the usefulness of determining the "stable" urinary protein levels of functional molecules in patients with glomerular diseases (Stangou et al 2009(Stangou et al , 2013Watson et al 2012;Abujam et al 2013;Korzeniecka-Kozerska et al 2013). Among such candidate urinary cytokines/chemokines, monocyte chemoattractant protein-1 (MCP-1) has been reported to be a possible biomarker reflecting glomerular inflammation in patients with LN and IgAN (Stangou et al 2009(Stangou et al , 2013Watson et al 2012;Abujam et al 2013), since glomerular expression of MCP-1 is actually involved in the pathogenesis and subsequent tissue injury (Marks et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical studies of IgAN, patients with moderate to severe disease showed much higher renal MCP-1 mRNA and protein expression, and higher levels of urinary MCP-1, compared with patients with mild and nonprogressive disease. Urinary levels of IL-6 and IL-8 also correlate with histological lesions and levels of proteinuria (32)(33)(34). Furthermore, levels of renal gene expression of various cytokines and chemokines, including TNF-a, IL1b, IL-6, IL-8, and IFN-g, correlate with the pattern and extent of histological lesions and clinical findings (35).…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have associated CCL2/MCP-1 with glomerulopathies [6,13,[19][20][21][22][23][24][25][26] and with renal transplantation [10,27,28]. Wada and coworkers found significantly elevated urinary levels of this chemokine in adults with diabetic nephropathy, whereas serum levels remained similar to those of healthy volunteers [21].…”
Section: Chemokines In Renal Diseasesmentioning
confidence: 99%
“…CCL2/MCP-1 was the first CC chemokine to be discovered, acting as a potent chemotactic factor for monocytes, and has been one of the most studied biomarkers [6,10,13,[17][18][19][20][21][22][23][24][25][26][27][28]. Many studies have associated CCL2/MCP-1 with glomerulopathies [6,13,[19][20][21][22][23][24][25][26] and with renal transplantation [10,27,28].…”
Section: Chemokines In Renal Diseasesmentioning
confidence: 99%